Trophodynamics of mesozooplankton in the the vicinity of the subtropical convergence in the Indian sector of the Southern Ocean - Daly, Ryan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
The trophodynamics of the numerically dominant mesozooplankton (200-2000 m) in the vicinity of the Subtropical Convergence (STC) in the Indian sector of the Southern Ocean during austral autumn (April / May) 2007 were investigated as part of the Southern Ocean Ecosystem Variability Study. The survey consisted of six north-south transects each bisecting the STC between 38º to 43ºS and 38º to 41º45'E. In total, 48 stations situated at 30 nautical mile intervals were occupied over a period of ten days. Hydrographic data revealed a well defined surface and sub-surface expression of the STC, which appeared to meander considerably between 41ºS and 41º15'S. Surface chlorophyll-a (chla) concentrations were low, ranging between 0.08 and 0.68 mg chl-a.m-3 and were generally dominated by the picophytoplankton (<2 m) which made up 66.6% (SD±17.6) of the total pigment. Chl-a concentrations integrated over the top 150m of the water column ranged between 11.97 and 40.07 mg chl-a.m-2 and showed no significant spatial patterns (p>0.05). Total integrated mesozooplankton abundance and biomass during the study ranged between 3934.9 and 308521.4 ind.m-2 (mean = 47198.19; SD±62411.4 ind.m-2) and between 239.8 and 4614.3 mg Dwt.m-2 (mean = 1338.58; SD ±1060.5), respectively. Again, there were no significant spatial patterns in the total mesozooplankton abundance or biomass within the region of study (p>0.05). No significant correlations were found between biological (chlorophyll-a concentrations and zooplankton abundance) and physico-chemical variables (temperature and salinity) (p>0.05). The total mesozooplankton community was numerically dominated by copepods of the genera Pleuromamma, Calanus, Oncaea and Oithona. Other important representatives of the mesozooplankton community included the tunicate, Salpa thompsoni, and the pteropod, Limacina retroversa. At the 40% similarity level, numerical analysis identified five distinct mesozooplankton groupings within the survey area. Differences between the groupings were associated with changes in the relative contribution of numerically dominant species rather than the presence or absence of individual species. No groupings were associated with any specific feature of the front within the survey area. The feeding rates of the six most numerically abundant mesozooplankton species (Calanus simillimus, Limacina retroversa, Pleuromamma abdominalis, Clausocalanus breviceps, Oncaea conifera, Salpa thompsoni) accounting for on average 39% of the total mesozooplankton counts, were investigated using the gut fluorescence technique. For all species, the total gut pigment contents during the night time were significantly higher than the daytime values (p<0.05 for all species). The gut evacuation rates (k) for selected mesozooplankton ranged between 0.14 and 0.81 h-1. The ingestion rates ranged between 147.8 and 5495.4 ng(pigm)ind-1.day-1 which corresponded to a daily ration of between 2.4 and 10.9% body carbon. The combined grazing impact of the selected species on the daily phytoplankton standing stock was highly variable and ranged between 1.2 and 174.1% with an average of 27.3% (SD±38.78%) within the survey area. The highest grazing impact (>60%) was typically associated with those stations where the pteropod, L. retroversa, and the tunicate, S. thompsoni, contributed more than 5% of the total mesozooplankton counts. No significant differences were found in the grazing impact of any or all selected species situated either north, south or in the immediate vicinity of the front (p>0.05 in all cases). The lack of defined spatial patterns in the mesozooplankton abundance and community structure suggests that the STC did not act as a significant biogeographic barrier to the distribution of mesozooplankton during the study. It is presumed that the large scale mixing event caused by a storm prior to this study was responsible for the observed lack of elevated biological activity within the region of the STC.
Keywords: Zooplankton -- Antarctic Ocean; Phytoplankton -- Antarctic Ocean